Aspectos éticos em dissertações e teses do PPGE/UFSCar à luz da resolução CNS 196/96 - Siquelli, Sônia Aparecida (Universidade Federal de São Carlos, 2011)
This doctoral thesis has been developed in order to identify the ethical aspects of research in education, considering the 196/96 National Health referred to the guidelines and standards regulated research involving humans. To make it possible to perform this task and establish the theoretical research we used the reflection on the concept of ethics and ethics in life science research. The methodological approach was based on bibliometrics that were used to analyze the scientific production of 73 theses and dissertations in the Graduate Program in Education (PPGE) of the Federal University of São Carlos (UFSCar), between January 2009 and December 2010. This historical period was chosen because of the concern in describe and discuss the ethical aspects of research produced in the first decade of this century, and questionnaires, with a former student and three teachers linked to the Program. The results of bibliometric analysis allowed to verify that participants were 2606 of these dissertations and theses and that 74% of the studies analyzed (21 theses and dissertations 33) were not submitted to the Ethics Committee. Analysis of the questionnaires revealed that participants are aware of the demands of ethical commitment in conducting research, but in different degrees of depth, particularly with respect to the contents of Resolution CNS 196/96. Participants also agreed on the need for further clarification on the ethics of research to graduate students, and emphasized that the bureaucratic aspects surrounding the submission of research to the Research Ethics Committees, often away from the researchers. Finally, it was observed that the participants consider that studies performed in this field of knowledge does not pose risks to the participants surveyed, which points to the importance of building a culture of bioethics needed for academic and professional researchers in education, because all intervention research entails risk to the participant, and for small or rare they are, must be provided.
Keywords: Educação; Ética em pesquisa; Resolução CNS 196/96.; Teses e dissertações análise bibliométrica; Ethics; Education; CNS Resolution 196/96; Theses and dissertations - bibliometric analysi.; CIENCIAS HUMANAS::EDUCACAO